Challenges and innovation: Disease modeling using human-induced pluripotent stem cell-derived cardiomyocytes - Reilly, Louise; Munawar, Saba; Zhang, Jianhua; Crone, Wendy C.; Eckhardt, Lee L. (Frontiers in Cardiovascular Medicine, 2022)
Disease modeling using human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) has both challenges and promise. While patient-derived iPSC-CMs provide a unique opportunity for disease modeling with isogenic cells, the challenge is that these cells still demonstrate distinct properties which make it functionally less akin to adult cardiomyocytes. In response to this challenge, numerous innovations in differentiation and modification of hiPSC-CMs and culture techniques have been developed. Here, we provide a focused commentary on hiPSC-CMs for use in disease modeling, the progress made in generating electrically and metabolically mature hiPSC-CMs and enabling investigative platforms. The solutions are bringing us closer to the promise of modeling heart disease using human cells in vitro.